Granulomatosis with Polyangiitis with Bilateral Facial Palsy and Severe Mixed Hearing Loss - Agnieszka Wawrzecka; Anna Szymańska; Radosław Jeleniewicz; Marcin Szymański (Case Reports in Otolaryngology)
Granulomatosis with polyangiitis is autoimmune and rare disease. It affects many organs, but the most often affected organs are the nose, lungs, and kidneys. It is part of vasculitis and causes an autoimmune attack by an abnormal type of circulating antibody termed ANCAs against small blood vessels. Disease concerns both men and women with a peak age of presentation in the sixth and seven decades. Typically upper and lower respiratory tract and kidneys are involved. Otitis externa, otitis media, or mastoiditis rarely occurs in granulomatosis with polyangiitis. Deafness is the most dangerous aural complication. Histological examination of biopsy is often not specific. A case of GPA with bilateral otitis media, bilateral deafness, and bilateral facial palsy with fatal course is presented.